COVID-19 computed tomography reporting systems: inter- rater and inter-system agreement study - Koc, Ural; Unal, Ozlem; Ozkan, Erdem; Kayaaslan, Bircan (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate agreements between COVID-19 reporting systems and radiologists.Materials and Methods: A total of 100 laboratory-confirmed COVID-19 cases (49 males, 51 females; age range 19-88 years) wereretrospectively collected. Firstly, computed tomography (CT) images were evaluated by two radiologists independently and blindedto clinical notes and laboratory and radiological reports and they gave their impressions independently according to four COVID-19reporting systems, then all CTs were interpreted again by the two radiologists for extracting CT features at the same session byconsensus.Results: Bilateral, lower lobe, peripheral, dorsal and multifocal lung involvements were predominantly seen, and ground-glassopacities (GGOs) were the most common CT imaging finding in the current study. Reporting systems showed fair to moderateagreements between senior and junior raters (0.246-0.490, p
Keywords: Coronavirus; COVID-19; radiology information systems; tomography